Nâng cao vai trò của phụ nữ trong sản xuất nông nghiệp thích ứng với biến đổi khí hậu tại vùng đồng bằng sông Cửu Long: Trường hợp nghiên cứu Hợp tác xã Nông ngư Hoà đê - Em, Nguyễn Văn Nhiều; Đông, Khưu Thị Phương; Trang, Lê Thị Thu; Thư, Tất Duyên; Thảo, Nguyễn Thị Phương; Minh, Nguyễn Nguyên; Trung, Nguyễn Hiếu (Tạp chí Khoa học Đại học Cần Thơ, 2025)
This study aims to identify solutions enhancing the role of women in climate-adaptive agricultural production, using the case of Hoa De Agro-Aquaculture Cooperative as a representative example. Data were collected using the Participatory Rural Appraisal (PRA) method with 21 cooperative members, incorporating the GEDSI framework throughout the data collection and analysis process. The results show that women play a key role in both agricultural and non-agricultural activities, particularly in value-added processes. However, they continue to face numerous barriers in accessing resources, information, technical knowledge, and leadership positions. These barriers stem from social, gender-based, institutional, policy-related factors, as well as the impacts of climate change. Based on the findings, the study suggests some policy implications to enhance women’s rights and status, including improved access to credit, technical training, market access support, and encouragement of female leadership. This study successfully applied the GEDSI framework to analyze the role of women in the shrimp-rice farming model, thereby providing new empirical evidence in the context of Cooperatives.